The beneficial efficacy of liposomal resveratrol against doxorubicin-induced hepatotoxicity in rats: Role of TGF-β1 and SIRT1 - Ahlam M. Alhusaini (Elsevier, 2021)
Objectives: Doxorubicin (DOXR) belongs to the antineoplastic anthracycline antibiotic and despite its prevalent use for various types of cancer, it is associated with side effects that occur even after treatment cessation, particularly on the heart, blood, liver and kidney. This study aimed to study the efficiency of carvedilol (CAR), resveratrol (RES) or liposomal RES (LIPO-RES) and their combination to treat DOXR-induced hepatotoxicity and to investigate other driving mechanisms that are involved. Methods: Rats were injected twice weekly with DOXR for five weeks to induce liver injury. A week before DOXR injection commenced, rats were pretreated singly or simultaneously with CAR, RES or LIPO-RES for six weeks. Results: The significant elevation in serum alanine aminotransferase (ALT) and the changed the hepatic tissue structure following DOXR administration indicating hepatic injury. Additionally, DOXR injection caused upregulation of the hepatic malondialdehyde (MDA), inflammatory cytokines, and transforming growth factor-β1 (TGF-β1) levels. The endogenous glutathione (GSH) and sirtuin1 (SIRT1) expressions in the liver were downregulated following DOXR administration. CAR, RES or LIPO-RES as their alternative combinations attenuated the liver injury by controlling oxidative stress, inflammation, and fibrosis. These beneficial effects were apparent upon using combined CAR and LIPO-RES, as proved by restoring the balance of MDA and GSH levels, decreasing hepatic cytokines levels of IL-6 and TNF-α, upregulating SIRT1 and downregulating TGF-β1 levels. Conclusion: The current study indicated that the use of CAR, RES or LIPO-RES alone or in combination could prevent DOXR-induced hepatic damage in rats by inhibiting oxidative stress, inflammation, and fibrosis.